Scholarship in action. Issue 2 (4th March 2017) - Baume, David
Abstract: Baume and Popovic describe three complementary and connected approaches to being scholarly in higher education – reflecting critically on practice, using the literature and contributing to the literature. Subsequent work reported here applies and tests the model in three settings – a meeting of the Southern Africa Universities Learning and Teaching Forum (SAULT); a seminar for senior staff in support of an institutional wide curriculum revision project at the National University of Lesotho; and a Professional Doctorate (EdD) seminar at London South Bank University. Reflecting critically on these experiences, the article explores some relationships between stages of the model, and thereby extends the model a little. More broadly the article suggests how an explicitly scholarly practice can permeate our work in universities. The article also tries to show a reflective and scholarly approach in action, and perhaps to demystify and even de-problematise a little the concept of scholarship.